Preclinical evaluation of the ANCD thrombectomy device: safety and efficacy in a swine clot model. (20th January 2020) - Sanchez, Sonia; Bailey, Lynn; Ducore, Rebecca; Andersson, Tommy; Nogueira, Raul; Cognard, Christophe; Ribo, Marc; Villanova, Helena; Rios, Anna; Galve, Iñaki
Abstract : Background: The Advanced Thrombectomy System (ANCD) provides a new funnel component designed to reduce clot fragmentation and facilitate retrieval in patients with stroke by locally restricting flow, allowing distal aspiration in combination with a stent retriever (SR). Objective: To evaluate the preclinical efficacy and safety of the ANCD in a swine clot model. Methods: Soft and firm clots were implanted in the lingual and cervical arteries of 11 swine to obtain Thrombolysis in Cerebral Infarction (TICI) 0 blood flow. Mechanical thrombectomy was performed with either a balloon guide catheter+Solitaire 2 stent retriever (BGC+SR, n=13) or ANCD+SR (n=13). TICI flow was evaluated and successful revascularization was defined as TICI 3 (normal perfusion). To characterize safety, a total of 3 passes were performed in each vessel independent of recanalization. Tissues were explanted for histopathological analysis after 3 and 30 days, respectively. Results: First pass reperfusion rates were ANCD+SR: 69% and BGC+SR: 46%. Reperfusion increased after the third pass in both groups (ANCD+SR: 100%, vs BGC+SR: 77%). Recanalization was achieved after an average of 1.4 and 1.9 passes in ANCD+SR and BGC+SR (p=0.095), respectively. Vessel injury was comparable in both groups; endothelial loss at 3 days was the most common injury seen (ANCD+SR: 1.78±1.22; BGC+SR: 2.03±1.20; p=0.73), while other histopathological markers were absent or minimal. Tissues downstream from targeted vessels also showed absence or minimal lesions across both groups. Conclusions: Results in a swine clot model support the high efficacy of the ANCD+SR without causing clinically significant vessel injury potentially related to the new funnel component.